Prinsip Kepemimpinan Ketua Dewan Pastoral Stasi dalam Perspektif Seruan Apostolik Evangelii Gaudium - Timmi Malau; Petrus Simarmata; Josep Sianturi (Jurnal Ilmiah Religiosity Entity Humanity (JIREH), 2026)
This study aims to describe and analyze the leadership of the Heads of Station Pastoral Councils in Rayon Tiga Baru of the Beato Dionysius Sumbul Parish from the perspective of Evangelii Gaudium. The study employed a descriptive qualitative method. The results indicate that the leadership of the Heads of Station Pastoral Councils is manifested through ministry rooted in spirituality and the joy of the Gospel, exemplary Christian witness, attentiveness to the needs of the faithful, preferential concern for the poor and those facing difficulties, the promotion of dialogue and communal solidarity, contextual evangelization grounded in local culture, active involvement of the laity, and openness to ongoing pastoral renewal. These findings demonstrate that pastoral leadership is not merely oriented toward administrative functions but is characterized by a missionary, participatory, inclusive, and context-sensitive approach that remains close to the realities of the faithful. This study affirms that the principles of Evangelii Gaudium can be concretely actualized in pastoral leadership at the station level and contribute to the enrichment of pastoral leadership studies oriented toward communion, participation, mission, and ecclesial renewal.